Durability of green rubberized 3D printed lightweight cement composites reinforced with micro attapulgite and micro steel fibers: Printability and environmental perspective - Bodur, Burak; Mecit Işık, Muhammet Ahmet; Benli, Ahmet; Bayrak, Barış; Öz, Ali; Bayraktar, Oguzhan Yavuz; Kaplan, Gökhan; Aydın, Abdulkadir Cüneyt (Elsevier BV, 2024)
The increasing amount of tires manufactured annually worldwide has made waste tire management a major environmental concern. The goal of this work is to investigate the potential applications of waste tire aggregates (WTA) in a novel class of affordable, recycled composite materials. This study assesses the material behavior of rubberized 3D printed lightweight cement composites (3DLC) reinforced with raw micro attapulgite (ATP) and micro steel fibers (MSF) using WTA as a 100 % replacement for fine aggregate manufactured through 3D printing. The paper takes advantage of 3D concrete printing's advantages and addresses the environmental issues associated with waste tires. The extrudability and buildability properties of 3DLC are determined in the fresh state. Physical and thermal properties of 3DLC were determined. Mechanical properties of 3DLC including compressive, flexural, shear strength and flexural toughness were assessed. 3D printed samples were exposed to high temperature and sulfate (MgSO4), and their durability properties were determined. The microstructures of the mixes was analyzed. The CO2 emissions and costs of the blends were also assessed. The outcomes revealed that, the 3DLC mixture with 10 % ATP and 2 % MSF showed the greatest compressive strength performance, with increases of 17.82 and 29.51 % at 28 and 90 days, respectively relative to the mixture without ATP. Regardless of MSF level, at 28 and 90 days, all mixes with 10%ATP content showed the largest flexural strengths. The 3DLC mixture with 10 % ATP and 2 % MSF had the highest measured thermal conductivity. The blends with 20 % ATP and 0 % MSF showed the lowest thermal conductivity. The mixture containing 10 % ATP and 2 % MSF demonstrated the greatest high temperature performance, demonstrating strength enhancement of 21.85, 6.72 and 3.36 % at 200,400 and 600 degrees C respectively. Replacing cement with 10 and 20%ATP greatly increased the sulfate resistance of 3DLC mixtures and the mixture with 20%ATP and 2%MSF exhibited the best sulfate performance. The lowest CO2 emission and cost were determined for the mixture containing 20%ATP and 0%MSF (A20S0).
Keywords: Micro Steel Fibers; Micro Attapulgite; Mechanical Properties; Waste Tire Aggregates; d Printed Lightweight Composites; Durability